Embedded Wireless Communication Platform Addresses Crane Safety and Efficiency - Rahnamayiezekavat, Payam; Bernold, L. (2014)
Boosting the communication at the process level has been identified as a promising strategy to improve construction productivity, safety, and quality. However, the capacity of classic paper-based information flow at work-front limits the transformation toward a construction paradigm able to access a ubiquitous data network. For this reason, "information superhighways" have to be constructed to connect the many information sources and sinks to enable highly productive practices supported by built-in smart agents. Not only is IT an essential tool for linking islands of information needed, but it opens opportunities for processing the data in real time using sophisticated processes. Included in the discussion are the lessons learned on the site-readiness to accommodate IT and incentives to foster collaboration, creation of rugged interfaces, and interoperability. The paper ends with an analysis of the data collected during the experimental testing of innovative prototype systems that encompassed the use of RFID tags, GPS, the Electronic Construction Kiosk (eCKiosk), wireless IP camera, and Bluetooth intercom. Results confirm the importance of involving the site personnel in the implementation of new concepts and the positive effects of a well-designed IT system to improve significantly process productivity and quality. Practical challenges caused by the nature of construction are highlighted